Korupsi di Indonesia: Mengapa Pendekatan Pancasila Lebih Fundamental dan Efektif untuk Pemberantasan yang Berkelanjutan - Finanda, Aulya Helsa Putri; Mirza Difa Putri Ansori; Septia Putri Ramadhani; Melanie Anatasya Subroto; Diva Dwi Rahmatillah Mughni; Kusnul Khotimah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Corruption in Indonesia remains a serious problem that has been deeply rooted for a long time and has widespread impacts, both on the economic and social aspects, as well as on public trust in the government. Various eradication efforts have actually been undertaken, including through the trident strategy of the Corruption Eradication Commission (KPK), but their implementation still faces many obstacles, such as weak bureaucracy, overlapping regulations, and a persistently evolving culture of corruption. This study aims to examine and analyze why the Pancasila-based approach is considered more fundamental and effective in achieving sustainable corruption eradication. The method used is a qualitative approach with a literature study technique, which involves reviewing various scientific sources, journals, and official documents related to corruption and the values of Pancasila. The results of the study show that corruption is not merely a legal violation, but is also closely related to issues of values and culture. Therefore, a more comprehensive approach is needed. Pancasila, as the state foundation, contains moral, ethical, and spiritual values capable of shaping individual character while encouraging the creation of a system that is transparent, accountable, and just. Thus, the internalization of Pancasila values is considered more effective because it is not merely repressive, but also preventive and educational, thereby being able to support sustainable corruption eradication.